2021
DOI: 10.1080/14017431.2021.1889655
|View full text |Cite
|
Sign up to set email alerts
|

The duration of mediastinal chest tube drainage is not associated with postoperative pain or opioid consumption after cardiac surgery

Abstract: Objectives. Mediastinal chest tubes are considered to be a significant factor causing postoperative pain after cardiac surgery. The aim of the study was to ascertain whether the duration of mediastinal drainage is associated with postoperative pain and opioid consumption. Design. A total of 468 consecutive patients undergoing cardiac surgery at the Tampere University Hospital between December 2015 and August 2016 were retrospectively analyzed. The first 252 patients were treated according to short and the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…72 With respect to pain and opioid analgesia, Kalli and colleagues recently reported that the amount of postoperative pain or need for opioids was not affected by shorter chest tube duration after cardiac surgery. 73 These results associated with removal are preliminary, and their findings remain to be confirmed. An ongoing, single-center, prospective RCT (NCT04487262) is currently evaluating the timing of chest tube removal in adult cardiac surgery patients, comparing early postoperative pain, consumption of analgesic drugs, incidence of infection, and early postoperative respiratory function on postoperative day 0 and day 1 in 1,300 consecutive patients undergoing elective open heart surgery.…”
Section: Removal Criteriamentioning
confidence: 89%
See 2 more Smart Citations
“…72 With respect to pain and opioid analgesia, Kalli and colleagues recently reported that the amount of postoperative pain or need for opioids was not affected by shorter chest tube duration after cardiac surgery. 73 These results associated with removal are preliminary, and their findings remain to be confirmed. An ongoing, single-center, prospective RCT (NCT04487262) is currently evaluating the timing of chest tube removal in adult cardiac surgery patients, comparing early postoperative pain, consumption of analgesic drugs, incidence of infection, and early postoperative respiratory function on postoperative day 0 and day 1 in 1,300 consecutive patients undergoing elective open heart surgery.…”
Section: Removal Criteriamentioning
confidence: 89%
“…With respect to pain and opioid analgesia, Kalli and colleagues recently reported that the amount of postoperative pain or need for opioids was not affected by shorter chest tube duration after cardiac surgery. 73…”
Section: Chest Drain Practicesmentioning
confidence: 99%
See 1 more Smart Citation